2020
DOI: 10.1002/htj.21895
|View full text |Cite
|
Sign up to set email alerts
|

A parametric study of a photovoltaic panel with cylindrical fins under still and moving air conditions in Iraq

Abstract: Photovoltaic (PV) panel temperature plays a vital role in the performance of PV panels. When PV temperature increases, the electrical power and efficiency decrease. In the present study, a simple simulated model is derived and implemented for a 70-W finned PV panel and the results are compared with those for a reference (unfinned) PV panel. The effect of various parameters including fin diameter, fin height, ambient temperature, fin coverage-to-area ratio, and solar irradiance level on PV performance are exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…The set of empirical Correlations (A1) -(A7) used to estimate the air properties, which are functions of bulk fluid temperature and proportionally non-linear [38,80]…”
Section: Appendix a Air Propertiesmentioning
confidence: 99%
“…The set of empirical Correlations (A1) -(A7) used to estimate the air properties, which are functions of bulk fluid temperature and proportionally non-linear [38,80]…”
Section: Appendix a Air Propertiesmentioning
confidence: 99%
“…Furthermore, the configurations with fin lengths of 25, 30, and 35 mm allowed better cooling of the PV panel. A parametric study was conducted by Farhan et al 11 to assess the impact of cylindrical fins on the performance of the PV module under a natural convection condition. They concluded that the finned PV system generated about 3.32 kW·h more than unfinned PV during the summer season.…”
Section: Introductionmentioning
confidence: 99%